Drug Delivery Systems Based on Titania Nanotubes and Active Agents for Enhanced Osseointegration of Bone Implants - Ion, Raluca; Necula, Madalina Georgiana; Mazare, Anca Valentina; Mitran, Valentina; Neacsu, Patricia; Schmuki, Patrik; Cimpean, Anisoara (Current Medicinal Chemistry, 2020)
TiO2 nanotubes (TNTs) are attractive nanostructures for localized drug delivery. Owing to their excellent biocompatibility and physicochemical properties, numerous functionalizations of TNTs have been attempted for their use as therapeutic agent delivery platforms. In this review, we discuss the current advances in the applications of TNT-based delivery systems with an emphasis on the various functionalizations of TNTs for enhancing osteogenesis at the bone-implant interface and for preventing implant-related infection. Innovation of therapies for enhancing osteogenesis still represents a critical challenge in regeneration of bone defects. The overall concept focuses on the use of osteoconductive materials in combination with the use of osteoinductive or osteopromotive factors. In this context, we highlight the strategies for improving the functionality of TNTs, using five classes of bioactive agents: growth factors (GFs), statins, plant derived molecules, inorganic therapeutic ions/nanoparticles (NPs) and antimicrobial compounds.
CRIS-Team Scopus Importer:2020-03-31
Keywords: antibiotics; drug delivery; flavonoids; growth factors; inorganic ions; nanoparticles; osseointegration; statins.; TiO2 nanotubes